Genetic dissection of QTLs for oil content in four maize DH populations - Zhang, Xiaolei; Wang, Min; Guan, Haitao; Wen, Hongtao; Zhang, Changzheng; Dai, Changjun; Wang, Jing; Pan, Bo; Li, Jialei; Liao, Hui (Frontiers in Plant Science, 2023)
Oil is one of the main components in maize kernels. Increasing the total oil content (TOC) is favorable to improve maize quality by optimizing feeding requirement. To better understand the genetic basis of TOC, quantitative trait loci (QTL) in four double haploid (DH) populations were explored. TOC exhibited continuously and approximately normal distribution. The moderate to high broad-sense heritability (67.00-86.60%) indicated the majority of TOC variations were largely controlled by genetic factors. A total of 16 QTLs were identified across all chromosomes in a range of 3.49-30.84% in term of phenotypic variation explained. Among them, six QTLs were identified as the major QTLs that explained phenotypic variation larger than 10. Especially, qOC-1-3 and qOC-2-3 on chromosome 9 were recognized as the largest effect QTLs with 30.84% and 21.74% of phenotypic variance, respectively. Seventeen well-known genes involved in fatty acid metabolic pathway located within QTL intervals These QTLs will enhance our understanding of the genetic basis of TOC in maize and offer prospective routes to clone candidate genes regulating TOC for breeding program to cultivate maize varieties with the better grain quality.